Almost Sure Practical Exponential Stability of Nonlinear Disturbed Stochastic Systems with Guaranteed Decay Rate. Issue 6 (17th February 2017) - Barbata, Asma; Zasadzinski, Michel; Chatbouri, Ridha; Souley Ali, Harouna; Messaoud, Hassani
Abstract: In this paper, we consider nonlinear stochastic differential equations driven by multiplicative noises and affected by exogenous disturbances. Sufficient conditions are investigated for almost sure practical exponential stability of the non trivial solutions of these equations. A lower bound of the decay rate of these solutions is guaranteed.